Pediatric liver transplantation: A report from a pediatric surgical unit - Sanjay Rao; Ashley L. J. D'Cruz; Rajiv Aggarwal; Supraja Chandrashekar; G Chetan; Gayathri Gopalakrishnan; Stephen Dunn (Wolters Kluwer Medknow Publications, 2011)
Background: Liver transplantation is well established worldwide as an effective treatment for end-stage liver disease in children. Acceptance in India has been slow because of considerations of cost, infections, inability to support long-term care, and non-availability of expertise. Aim: This study was designed to report our experience with pediatric liver transplantation. Materials and Methods: Twenty-eight children underwent liver transplantation. Results: Biliary atresia was the commonest indication (n = 15) followed by metabolic liver disease. Twenty-six children had living donor transplants, mothers being the donors in a majority of these. Common surgical complications included bile leaks (n = 3) and vascular problems (n = 6). Common medical complications included infections, acute rejection, and renal failure. Overall, patient survival was 71%, while that for the last 14 cases was 92%. All survivors are doing well, have caught up with physical and developmental milestones and are engaged in age appropriate activities. Conclusions: The study demonstrates the feasibility of a successful pediatric liver transplant program in our country.